(untitled) (Cardiovascular Journal, 2012)
Background: Cardiologists play the major role in the management of hypertension in Bangladesh. Different classes of antihypertensive drugs are being used by the cardiologists in initiating hypertension treatment depending on the age and gender of the patient, severity of hypertension and associated diseases. However, there is no particular study to evaluate the patterns of the utilization of these antihypertensive drugs. Again, it is very important to use the right antihypertensive drug for the right patient to move further ahead in the management of hypertension. Hence, the current use of antihypertensive drugs in initiating hypertension treatment was analyzed. Methods: This was a nationwide survey with a participation of 196 cardiologists. Individual opinions from these cardiologists were collected through a questionnaire asking which antihypertensive they use most in initiating hypertension treatment. Collected data were analyzed by SPSS 17 software. Results: ACEI mono-therapy is the mostly used antihypertensive drug class for male patients aged < 55 years having mild to moderate hypertension. CCB mono-therapy is the mostly used antihypertensive drug class for female patients aged < 55 years having mild to moderate hypertension. CCB mono-therapy is also the mostly used antihypertensive drug class for both male and female patients aged e 55 years having mild to moderate hypertension. For severe hypertensive patients aged < 55 years, the mostly used antihypertensive drugs are combinations of ACEI+CCB+D for both male and females. For severe hypertensive patients aged e 55 years, the mostly used antihypertensive drugs are combinations of ACEI+CCB+D for males and combinations of CCB+BB for females. However, the overall pattern of using antihypertensive drugs did not significantly vary between male and female patients. Conclusion: The pattern of using antihypertensive drugs varies depending on age and gender of the patient and on the severity of hypertension. But, the overall pattern of using antihypertensive drugs did not significantly vary between male and female patients. DOI: http://dx.doi.org/10.3329/cardio.v4i2.10454 Cardiovasc. j. 2012; 4(2): 114-119